THE EFFECT OF PSYCHOLOGICAL CONTRACT VIOLATION ON WORKPLACE DEVIANCE: THE MEDIATING EFFECT OF TURNOVER INTENTION - Salin, Salin D.; Notelaers, Notelaers G. (International Journal of Current Practice in Management and Leadership (IJCPML), 2023)
This study examines the relationship between psychological contract violation (PCV), turnover intention (TI), and workplace deviance (WPD) among employees in the Agriculture and Food Directorates of Kenya. A total of 443 employees participated in the study by completing a structured questionnaire. The findings indicated that TI mediates the relationship between PCV and WPD. Furthermore, PCV has a negative influence on TI, while TI positively affects WPD. The study underscores the importance of the psychological contract between employee and employer, highlighting how violations can lead to negative attitudes at work and eventual turnover. The findings emphasize the need for human resource managers to address the problem of TI and develop appropriate mitigation strategies to reduce WPD. While the results are specific to a particular sector in Kenya, the implications for other industries and countries are significant. This study's contribution includes the identification of TI as a mediator between PCV and WPD, highlighting the importance of addressing TI as part of any efforts to reduce WPD.